Balancing Catch and Conservation: Mesh Size Modifications in Traditional Dol net Along the Mumbai Coast - Zaheer Abass; Karankumar Kishorkumar Ramteke; Abuthagir Iburahim; Binaya Bhusan Nayak; Asha T. Landge; Rajesh Kumar; Rinkesh Nemichand Wanjari; Naila M Bhat (Journal of Indian Fisheries Association, 2024)
Dol nets are traditional bag nets widely used in artisanal fisheries along the northwest coast of India, particularly in Maharashtra, where they play a crucial role in supporting small-scale fisheries. Despite their importance, dol nets have been criticized for their non-selective nature, leading to high bycatch and juvenile capture. This study aimed to modify the cod-end of dol nets by incorporating a 35 mm square mesh panel to enhance gear selectivity and promote sustainable fishing practices. Experimental fishing was conducted off Madh Island, Mumbai, to assess the impact of this modification on catch composition, species diversity, and catch efficiency. The results revealed a significant reduction in the capture of juvenile fish in the upper cod-end (average 8.42 kg per haul) compared to the lower cod-end (average 13.15 kg per haul), where smaller species and juveniles were concentrated. 48 species from 25 families were recorded, including finfish, shrimp, prawns, crabs, cephalopods, and mantis shrimp, with a noticeable decrease in species diversity compared to previous studies, likely due to the mesh modification. Incorporating the square mesh panel improved size selectivity, with larger, commercially valuable species retained in the upper cod-end while juveniles and smaller species were sorted into the lower compartment. These findings demonstrate that gear modifications, such as larger mesh panels, can significantly reduce bycatch, enhance fishing sustainability, and contribute to the conservation of fishery resources in the region. This study highlights the potential of blending traditional fishing practices with modern innovations to achieve sustainable fisheries management.